Key design parameters of a few types of electro-hydrostatic actuators for humanoid robots. (2nd December 2018) - Ko, Tianyi; Kaminaga, Hiroshi; Nakamura, Yoshihiko
ABSTRACT: To overcome the tradeoff between the bandwidth and force-to-weight ratio of the backdrivable actuators, actuation by electro-hydrostatic actuators (EHA) is effective. Based on the idea, we developed the adult size, humanoid robot 'Hydra', whose joints are driven by EHA. In its development, a critical problem was the insufficient force of the available lightweight and backdrivable EHA. In this paper, we present our approach to enhance their maximum force while keeping them small, lightweight and backdrivable. We first analyze the behavior of EHA and show that the maximum force is enabled on the balance between the viscous loss and the internal leakage loss. We also show that miniaturization of the actuator moves the system to the internal leakage loss dominant side, and to encounter this, reduction of the internal gap, maintain of the fluid viscosity, and full utilization of the space to enlarge the pressure receiving surface are effective. The mechanical design process and experimental evaluation on each of these three aspects are detailed. GRAPHICAL ABSTRACT: